2017
DOI: 10.1016/j.ajhg.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Monoallelic BMP2 Variants Predicted to Result in Haploinsufficiency Cause Craniofacial, Skeletal, and Cardiac Features Overlapping Those of 20p12 Deletions

Abstract: Bone morphogenetic protein 2 (BMP2) in chromosomal region 20p12 belongs to a gene superfamily encoding TGF-β-signaling proteins involved in bone and cartilage biology. Monoallelic deletions of 20p12 are variably associated with cleft palate, short stature, and developmental delay. Here, we report a cranioskeletal phenotype due to monoallelic truncating and frameshift BMP2 variants and deletions in 12 individuals from eight unrelated families that share features of short stature, a recognizable craniofacial ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…This protein belongs to the TGF-β superfamily, which has diverse biological activities related to bone physiology and metabolism [22,23]. Previous studies have found associations of the BMP-2 variants with bone and cardiac development, bone mineral density, as well as body size traits [24,25]. Also in human, BMP-2 appears to be the most important BMP affecting the adult skeleton [44].…”
Section: Potential Independent Of Positive Selection In the Dbp Populmentioning
confidence: 99%
“…This protein belongs to the TGF-β superfamily, which has diverse biological activities related to bone physiology and metabolism [22,23]. Previous studies have found associations of the BMP-2 variants with bone and cardiac development, bone mineral density, as well as body size traits [24,25]. Also in human, BMP-2 appears to be the most important BMP affecting the adult skeleton [44].…”
Section: Potential Independent Of Positive Selection In the Dbp Populmentioning
confidence: 99%
“…Seven homozygous KI mice, from different litters, survived past weaning age and were subjected to further evaluation for gross phenotypic and skeletal changes. We performed computerized tomography (µCT) whole-body scans of heterozygous ( Col27a1 G682R/+ ) and homozygous ( Col27a1 G682R/G682R ) KI mice and WT littermates to evaluate for gross skeletal abnormalities and reduced body length as a surrogate for the short stature phenotype observed in the human subjects [ 27 ]. We measured the snout to base of the tail (at caudal vertebra 4, CA4) distance to evaluate differences in body length among the heterozygous, homozygous, and WT mice.…”
Section: Resultsmentioning
confidence: 99%
“…This protein belongs to the TGF-β superfamily, which has diverse biological activities related to bone physiology and metabolism [17,18]. Previous studies have found associations of the BMP-2 variants with bone and cardiac development, bone mineral density, as well as body size traits [19,20]. Also in human, BMP-2 appears to be the most important BMP affecting the adult skeleton [21].…”
Section: Potential Independent Of Positive Selection In the Dbp Populmentioning
confidence: 99%